Potential Partnership of Community-based Management in Supporting The Utilization of Sustainable Resources in Indonesian Coastal Tourism - Saiqa Ilham Akbar; Anisa Nurpita; Elton Buyung Satrianto (Politeknik Negeri Batam, 2020)
The application of community-based management (CBM) in managing coastal tourism in Indonesia is still limited to providing short-term benefits, especially for local communities and does not guarantee the sustainability of resources at large. On the other hand, most CBM partnership in Indonesia are still limited to the relationship between the local government and local communities and there is no clear partnership scheme in involving the role of third parties and private sectors that can increase the benefits of implementing CBM. This study aims to review and evaluate CBM policies and implementation in the coastal tourism in Indonesia, identifies the effectiveness of CBM implementations, and suggest an optimal CBM partnership scheme in the coastal tourism in Indonesia. The data used are primary data through questionnaires, interviews, and focus group discussion (FGD). Respondents in this study include members of hotel and restaurant association, CBM managers, local government, and businessmen in the coastal tourism area. This study uses investment attractiveness index to measure the effectiveness of CBM in each coastal tourism destination. The findings shows that the implementation of CBM in Indonesian coastal tourism mostly favored the local communities but draws little attention from bigger investment mainly because there is a lack of clear land regulation set by local government in coastal area.